EXPLORING ASSOCIATIONS BETWEEN SELF-EFFICACY, WORK ENGAGEMENT AND BEHAVIORAL INTENTION TO USE GAMIFICATION - Alina IONESCU-CORBU; Andreea URSU; Gabriel CRAMARIUC (Association of Social and Educational Innovation, 2023)
Along with the growing interest and the continuous development in technology, gamification gained more recognition in the educational areas. While knowledge concerning gamified approaches and their advantages in the classroom are better understood for student populations, less is investigated in terms of factors that drive teachers to use such approaches in the classroom. The present study investigated the associations between self-efficacy, teachers' work engagement, and behavioral intention to use gamification among 170 teachers, aged between 18 to 64 years old (M = 34.9; SD = 9.69), with a teaching experience ranging from almost one year to 44 years of experience (M = 8.71; SD = 9.62). Correlation analyses showed that there are associations between teachers' self-efficacy, teachers' work engagement, and behavioral intention to use gamification. This study showed that there are significant associations between self-efficacy, work engagement, and the behavioral intention to use gamification. These results stress out the need for more investigations on the personal characteristics of teachers that may be related to the use of gamified approaches in the classroom.